Formate-Free Metal-Organic Decomposition Inks of Copper Particles and Self-Reductive Copper Complex for the Fabrication of Conductive Copper Films - Yuki Kawaguchi, Yuki Kawaguchi; Ryuichi, Ryuichi; Kawasaki, Hideya (Journal of Coating Science and Technology, 2016)
Metal-organic decomposition (MOD) inks have been developed for printed electronics applications. Cu-based MOD inks prevent the oxidation of the metal during storage, as the Cu is already present in an oxidized form (i.e. a salt). However, usually hazardous formates such as Cu (II) formate have to be used as the copper salt in order to ensure thermal decomposition and self-reduction of the metal salt at moderate temperatures (less than 150°C). In this study, a formate-free hybrid ink containing copper particles and a Cu/1-amino-2-propanol (AmIP)/acetate complex was developed for the fabrication of conductive copper films on flexible polymer substrates at low sintering temperatures. A hybrid ink with a weight ratio of 3:1copper particles to MOD ink produced a conductive copper film with close-packed copper particles and a low resistance of 7.3—10-5Ω cm after sintering at a temperature of 180°C for 60 min under a N2 gas flow. Good oxidation resistance of the copper films was observed after exposure to air at 23 Â°C for two months.